2014
DOI: 10.3164/jcbn.14-41
|View full text |Cite
|
Sign up to set email alerts
|

Intra-gastric pH following single oral administrations of rabeprazole and esomeprazole: double-blind cross-over comparison

Abstract: Comparisons between the acid inhibitory effects of rabeprazole and esomeprazole after single oral administration with standard doses have not been previously presented. We examined intra-gastric pH after oral administrations of these two proton pump inhibitors using 24-h pH monitoring. Fifty-four normal volunteers not infected by Helicobacter pylori were investigated. Using a cross-over design, we administered 10 mg of rabeprazole or 20 mg of esomeprazole in 27 at 30 min after supper and in the remaining 27 su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…(12,13) When patients had no history of eradication therapy, H. pylori infection was confirmed when any one of these tests was positive. After eradication therapy, cured status was confirmed via a 13 C-urea breath test.…”
Section: Methodsmentioning
confidence: 99%
“…(12,13) When patients had no history of eradication therapy, H. pylori infection was confirmed when any one of these tests was positive. After eradication therapy, cured status was confirmed via a 13 C-urea breath test.…”
Section: Methodsmentioning
confidence: 99%
“…In consideration of these results, the control of reflux symptoms that impair the quality of life [4] is of utmost importance when treating patients with mild RE. Although on-demand therapy with proton pump inhibitors (PPIs), has been reported as effective for patients with PPI-responsive non-erosive reflux disease and mild RE [1, 5, 6], it is impossible to obtain a gastric pH of 4 or above in a short time after administration of PPI [7, 8], and 3–5 days are necessary for consistent acid suppressive effects [9, 10]. Moreover, as the time of occurrence of reflux symptoms is unpredictable, continued PPI therapy is often indicated.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, which utilized a single PPI administration, we found that the acid suppressing effect of esomeprazole tended to be stronger than that of rabeprazole with preprandial administration, whereas the acid suppressing effect of rabeprazole tended to be stronger than that of esomeprazole with postprandial administration [14]. In the present study, we compared the acid suppressing effects between pre- and postprandial administrations of esomeprazole and rabeprazole after a 7-day period.…”
Section: Discussionmentioning
confidence: 99%
“…Such postprandial administration may present problems for difficult cases, as all PPIs available in Japan are thought to show a suboptimal acid suppressing effect with that administration protocol. However, few reports have noted a lowered acid suppressing effect with postprandial PPI administration [14,15,16]. In addition, esomeprazole is the only PPI for which plasma concentration and area under the curve (AUC) have been shown to be reduced after postprandial as compared to preprandial administration [15], and there is no known report that compared the acid suppressing effects of pre- and postprandial administrations of rabeprazole.…”
Section: Introductionmentioning
confidence: 99%